MODELS OF AUTOMATION OF CONTROL OF THE TECHNICAL STATE OF MARINE TRANSPORT - Коломієць, О. М. (Science-based technologies, 2019)
Analysis of the operation of water transport vehicles indicates the existence of contradictions, which consists, on the one hand, in the need to increase the technical readiness of ship equipment to the intended use and failures in its operation. For this purpose, it is necessary to carry out constant control over its operation and implementation of the whole complex of periodic inspections and diagnostics. At the same time, such an approach significantly increases the cost of operating equipment and reduces the overall profitability of the fleet. On the other hand, attempts to maximize the cost reduction of maritime transport, leads to a decrease in the number of control measures, simplification of their procedures (regulations), with the conversion of the maximum number of diagnostic functions to technical means. In this aspect, the development of new methods for the technical operation of equipment, based on the use of modern automated procedures for determining the frequency and scope of diagnosis is relevant. The article defines the principles of automation of the technical condition of water transport means: the principle of coherence; the principle of integration; principle of independence of execution. It is determined that the most effective strategy is to improve the model of automated control of the technical condition of water transport vehicles, which, unlike existing ones, is based on Markov processes, the Runge-Kutta method of numerical solution of the system of Kolmogorov differential equations and a priori information about the intensity of transitions from state to state. Using the software implementation of the model significantly improves performance due to the ergonomics of the interface and reduced number of operations. The simulation of the technical condition of water transport using software developed indicates that the development is functional because the software meets all the needs of the user. The model is adequate, and this software is quite reliable. The program interface is user-friendly and ergonomic.